Fluid Physics in Geology : an Introduction to Fluid Motions on Earth's Surface and within Its Crust. - Furbish, David Jon (Oxford University Press, 1997)
Preface Chapter 1: Introduction 1.1. Topics and Strategies in the Study of Fluid Physics1.2. Units and Mathematical Conventions1.3. Scope of Mathematics Used in This Text1.4. Example Problems1.5. ReadingChapter 2: Fluids and Porous Media as Continua 2.1. Mean Free Path2.2. Mathematical and Physical Points2.3. Representative Elementary Volume2.4. Example Problems2.5. ReadingChapter 3: Mechanical Properties of Fluids and Porous Media 3.1. Body and Surface Forces3.2. Ideal Versus Real Fluids3.3. Density3.4. Fluid Rheology and Shear Viscosity3.5. Compressibility3.6. Surface Tension3.7. Example Pro.